How the Personal Became Political: The Feminist Movement of the 1970s. Issue 95 (2nd January 2018) - Reid, Elizabeth
ABSTRACT: Elizabeth Reid (AO, FASSA, FAIIA) was the first adviser on women's affairs to any head of government in the world, appointed by Prime Minister Gough Whitlam in 1973. Drawing on her own life and writing, and those of other members of the Women's Liberation Movement and the Women's Electoral Lobby, Reid recreates the fire that burned in 1970s feminists. Weaving together connections between sexuality, justice, morality, and the cultural structures of sexism, Reid evokes women's experiences of personal disempowerment that fuelled their activism and political determination. In 1973 when the Prime Minister's office advertised for a Women's Adviser, feminists debated whether or not revolution could be made from within government. Reid recalls her work as Women's Adviser, and her leadership of the Australian delegation to the 1975 International Women's Year events in Mexico City. As the nation's most prominent feminist, Reid travelled around Australia and spoke to all kinds of women. She received more letters than any member of Cabinet other than the Prime Minister. In this significant retrospective, Reid summarises the achievements of the Whitlam Government in various areas, the constraints it faced, and more broadly the successes of the 1970s feminist movement and what we can learn from it now.